Engaging Faculty and Students Across Departments to Increase Community Engagement - Gale B. Rice PhD.,CCC-SLP; Carmen Russell PhD,CCC-SLP; Mary Beth Ohlms M.Ed-FACS; Jamie VanDycke PhD. (Academic Chairpersons Conference Proceedings, 2016)
This Brown Bag discussion will allow participants to both share results of their efforts to increase multi-disciplinary efforts of both faculty and students in the community and to brainstorm possibilities. These efforts foster collaborative problem-solving skills and increase name recognition of the university in the community.
Keywords: Brown Bag; Integration; Community; Multi-disciplinary